PENGARUH DIVIDEND PAYOUT RATIO, RETURN ON ASSET, DAN PENJUALAN TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Binsar Sihombing; Hendra Agustinus H. Marbun (Universitas Negeri Medan (UNIMED), 2017)
This research is intended to analyze the influence of dividend payout ratio, return on asset and sale to stock price of company in Indonesia Stock Exchange. To achieve this goal, Sampling in this study using purposive sampling method. The population used in this study is a manufacturing industry company registered in Indonesian Stock Exchange in 2009 as many as 153 companies, from the population taken 42 companies as a sample. The analysis was done by multiple linear regression model. From the results of the discussion is known that, dividend payout ratio, return on assets and sales have a positive influence on stock prices. Dividend payout ratio has a regression coefficient of 0.180311 with probability of 0.0847 or 8.47 percent. Return on asset has a regression coefficient of 0.54029 with a probability of 0.0093 or 0.93 percent. The sales order has a regression coefficient of 0.428178 with a probability of 0.0000 or 0 percent.Keywords: Dividend, Assets, Capital Market